UTERUS CANCER PROFILE IN WOMEN RESIDENTS IN MONTES CLEAR, MINAS GERAIS - da Silva Alves, Renato; Dias Sales Palma, Laryane; Lopes Amaral, Lais; Gabryella Viana, Letícia; Talita Santos Silva, Karla; Fernanda Costa Quadros, Joice; de Pinho Amaral, Bruno (Health and Society, 2021)
Introduction: Cervical cancer is one of the most frequent in the female population, it is related to HPV infection, multiple partners, unfavorable socioeconomic conditions, among other factors. Objective: To know the profile of cervical cancer in women living in Montes Claros, Minas Gerais, Brazil. Methods: This is a descriptive study with a quantitative approach using data from patients diagnosed with cervical cancer available in hospital records of the José Alencar Gomes da Silva National Cancer Institute (INCA). Results and discussion: In the period analyzed, 555 cervical cancer diagnoses were registered in the database of the José Alencar Gomes da Silva National Cancer Institute (INCA) in the municipality investigated. Conclusion: The data available in the INCA database in relation to women residing in Montes Claros, Minas Gerais indicated adult, married, brown women, with a low level of education and occupations with low wages. Coordinated actions from all public spheres of planning and execution of women's health policy are needed to intensify early diagnosis and treatment.